Research of the university education development in the Dutch pedagogical science - Zaiats, L. (Continuing Professional Education: Theory and Practice, 2019)
The article is devoted to the analysis of the research of the European university education development in the Dutch pedagogical science. The key aspects of the problem that had been studied by the Netherlands scientists are highlighted in the article. The author characterizes research works of the Netherlands scientists who consider the problem of the university education development in the context of Western Europe Higher Education Study. The author analyzes the activity of the main pedagogical research institutions, such as Center for Higher Education Policy Studies in the university of Twente and Rathenau Institute in Hague. The scientific works of such Netherlands researchers are analyzed in the article: Liudvika Leišytė (University governance and academic research. Case studies of research units in Dutch and English universities); Hendrikus Christiaan Theisens (The state of change. Analyzing policy change in Dutch and English higher education); Anneke Luijten-Lub (Choices in internationalisation: How higher education institutions respond to internationalisation, europeanisation, and globalization); Johanna Katharina Witte (Change of degrees and degrees of change. Comparing adaptations of European higher education systems in the context of the bologna process); Egbert de Weert, Patra Boezerooy (Higher education in the Netherlands); Katherine Chiong Meza (Universities in the Netherlands. Facts and figures). The author concludes that Dutch researchers gained significant material in studying of university education theory and practice. After the analyzing of these works author makes a conclusion about the high level of the Netherlands university education development and about advisability to study this experience for reforming Ukrainian higher education.